Axillary Nerve Position in Humeral Avulsions of the Glenohumeral Ligament. Issue 12 (30th November 2018) - Bokor, Desmond J.; Raniga, Sumit; Graham, Petra L.
Background: The axillary nerve is at risk during repair of a humeral avulsion of the glenohumeral ligament (HAGL). Purpose: To measure the distance between the axillary nerve and the free edge of a HAGL lesion on preoperative magnetic resonance imaging (MRI) and compare these findings to the actual intraoperative distance measured during open HAGL repair. Study Design: Case series; Level of evidence, 4. Methods: A total of 25 patients with anterior instability were diagnosed as having a HAGL lesion on MRI and proceeded to open repair. The proximity of the axillary nerve to the free edge of the HAGL lesion was measured intraoperatively at the 6-o'clock position relative to the glenoid face. Preoperative MRI was then used to measure the distance between the axillary nerve and the free edge of the HAGL lesion at the same position. Distances were compared using paired t tests and Bland-Altman analyses. Results: The axillary nerve lay, on average, 5.60 ± 2.51 mm from the free edge of the HAGL lesion at the 6-o'clock position on preoperative MRI, while the mean actual intraoperative distance during open HAGL repair was 4.84 ± 2.56 mm, although this difference was not significant ( P = .154). In 52% (13/25) of patients, the actual intraoperative distance of the axillary nerve to the free edge of the HAGL lesion was overestimated by preoperative MRI. In 36% (9/25), this overestimation of distance was greater than 2 mm. Conclusion: The observed overestimations, although not significant in this study, suggest a smaller safety margin than might be expected and hence a substantially higher risk for potential damage. We recommend that shoulder surgeons exercise caution in placing capsular sutures in the lateral edge when contemplating arthroscopic repair of HAGL lesions, as the proximity of the nerve to the free edge of the HAGL tear is small enough to be injured by arthroscopic suture-passing instruments.